Evolution of microstructure and mechanical properties of coated Co-base superalloys during heat treatment and thermal exposure - Webler, Ralf; Ziener, Marco; Neumeier, Steffen; Terberger, Philipp J.; Vassen, Robert; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2015)
WW1::1024
Keywords: High Temperature; Nanomechanics

Isothermal aging of a γ′-strengthened Co-Al-W alloy coated with vacuum plasma-sprayed MCrAlY bond coats - Terberger, Philipp J.; Sebold, Doris; Webler, Ralf; Ziener, Marco; Neumeier, Steffen; Klein, Leonhard; Virtanen, Sannakaisa; Göken, Mathias; Vassen, Robert (Surface & Coatings Technology, 2015)
WW1::1049
Keywords: High Temperature

The influence of niobium, tantalum and zirconium on the microstructure and creep strength of fully lamellar gamma/alpha(2) titanium aluminides - Bresler, Johannes; Neumeier, Steffen; Ziener, Marco; Pyczak, F.; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
Titanium aluminides are excellent materials for light-weight applications at high temperatures. To enhance their creep strength, various alloying elements are added. In this work the effect of 5 at% Niobium (Nb), Tantalum (Ta) and Zirconium (Zr) on the creep properties of ternary Ti-44Al-5X (X = Nb, Ta, Zr) with a fully lamellar microstructure, is systematically studied. These alloying elements have a high solubility in titanium aluminides, and show a different alpha(2)/gamma partitioning behavior as well as a different influence on the lattice parameters of both phases. The average interface distance between the alpha(2)- and gamma-phase is adjusted to about 300 nm by the cooling rate to evaluate the influence of the three alloying elements. The creep tests reveal that all three alloying elements increase the creep resistance of titanium aluminides, particularly Ta and Zr. Ta seems to extend the pronounced primary creep regime, whereas Zr seems to reduce it The alloying elements decrease also the lamellar spacing compared to the binary alloy. Microstructural investigations after the creep tests show a beneficial effect of the alloying elements on the microstructural stability during creep exposure, since they retard the discontinuous coarsening rate.
Keywords: Titanium aluminides; Microstructure; Alloying elements; Creep

The influence of niobium, tantalum and zirconium on the microstructure and creep strength of fully lamellar γ/α2 titanium aluminides - Bresler, Johannes; Neumeier, Steffen; Ziener, Marco; Pyczak, F.; Göken, Mathias (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2019)
Keywords: Alloying elements; Creep; Microstructure; Titanium aluminides